Different types of semi‐natural habitat are required to sustain diverse wild bee communities across agricultural landscapes. Issue 10 (9th August 2022) - Maurer, Corina; Sutter, Louis; Martínez‐Núñez, Carlos; Pellissier, Loïc; Albrecht, Matthias
Abstract: Semi‐natural habitats provide important resources for wild bees in agricultural landscapes. Landscapes under management are dynamic and floral resources fluctuate in space and time. Thus, promoting different semi‐natural habitat types within landscapes could be key to support diverse bee meta‐communities throughout the season. Here, we integrate analyses of α‐diversity (species richness) and β‐diversity and species‐habitat networks to examine the relative contribution of all major semi‐natural habitats to wild bee meta‐communities in agricultural landscapes. We sampled extensively and conventionally managed meadows, flower strips, hedgerows and forest edges in spring, early and late summer in 25 landscapes in Switzerland. Habitat types varied in their importance for wild bees throughout the season: While extensively managed meadows supported more rare species, habitat specialists and bee species overall than the other habitat types, flower strips were most important later in the season. Each of the five investigated habitat types harboured relatively unique sets of species with different habitats generally acting as distinct modules in the overall bee‐habitat network. Not only flower richness in a habitat per se, but also flower‐habitat network properties (habitat strength and functional complementarity) were good predictors of wild bee richness. In addition to local floral richness, landscape composition and configuration interactively influenced β‐diversity patterns across habitats. Synthesis and applications . Our study highlights the value of pollinator‐habitat network analysis to inform pollinator conservation management at the landscape scale, especially when combined with information on floral resources and flower‐habitat networks. Maintaining different types of semi‐natural habitats offers diverse and complementary resources throughout the season, which are crucial to sustain diverse wild bee meta‐communities in agricultural landscapes. Particularly meadow extensification schemes can play a key role in safeguarding rare and specialist species in these landscapes. While locally a high flower richness promoted bee abundance and richness in general, our results indicate that increasing connectivity between habitat patches in landscapes dominated by arable crops appears to improve species exchange between local bee communities of different habitats, thereby possibly increasing their resilience to disturbances. Abstract : Our study highlights the value of pollinator‐habitat network analysis to inform pollinator conservation management at the landscape scale, especially when combined with information on floral resources and flower‐habitat networks. Maintaining different types of semi‐natural habitats offers diverse and complementary resources throughout the season, which are crucial to sustain diverse wild bee meta‐communities in agricultural landscapes. Particularly meadow extensification schemes can play a key role in safeguarding rare and specialist species in these landscapes. While locally a high flower richness promoted bee abundance and richness in general, our results indicate that increasing connectivity between habitat patches in landscapes dominated by arable crops appears to improve species exchange between local bee communities of different habitats, thereby possibly increasing their resilience to disturbances. Zusammenfassung: Naturnahe Lebensräume bieten wichtige Ressourcen für Wildbienen in Agrarlandschaften. Diese bewirtschafteten Landschaften sind jedoch dynamisch, und die Verfügbarkeit von Ressourcen wie Blütenpflanzen kann stark variieren. Daher könnte die Förderung verschiedener Typen von naturnahen Lebensräumen der Schlüssel sein für den ganzjährigen Schutz artenreicher Wildbienengemeinschaften. In dieser Studie analysieren wir α‐Diversität (Artenzahl), β‐Diversität (Ähnlichkeit der Artzusammensetzung) und Art‐Lebensraum‐Netzwerke, um die relative Wichtigkeit der häufigsten naturnahen Lebensräume in Agrarlandschaften für artenreiche Wildbienengemeinschaften zu untersuchen. In 25 Landschaften in der Schweiz sammelten wir Daten zu Wildbienenarten in extensiv und konventionell bewirtschafteten Wiesen, Buntbrachen, an Hecken und Waldrändern im Frühling, Früh‐ und Spätsommer. Die verschiedenen Lebensraumtypen waren von unterschiedlicher Wichtigkeit für Wildbienen, je nach Zeitpunkt in der Saison. Während extensiv bewirtschaftete Wiesen generell mehr seltene Arten, Lebensraumspezialisten und mehr Bienenarten beherbergten als die anderen Lebensraumtypen, waren Buntbrachen vor allem im Juli wichtig. In jedem der fünf untersuchten Lebensraumtypen fanden wir eine relativ einzigartige Artzusammensetzung: Im Bienen‐Lebensraum‐Netzwerk gliederten sich die Lebensraumtypen in verschiedene Module. Nicht nur Blütenpflanzenvielfalt in einem Lebensraum, sondern auch Blütenpflanzen‐Lebensraum‐Netzwerk Eigenschaften («Lebensraum‐Stärke» und «funktionelle Komplementarität») konnten die Wildbienenvielfalt in einem Lebensraum voraussagen. Zusätzlich zur lokalen Blütenpflanzenvielfalt beeinflussten die Landschaftszusammensetzung und ‐konfiguration die β‐Diversität der Wildbienen (Ähnlichkeit der Artzusammensetzung) zwischen den Lebensraumtypen. Unsere Studie unterstreicht den Wert der Analyse von Bestäuber‐Lebensraum‐Netzwerken für die Förderung und den Schutz der Bestäuber auf Landschaftsebene, insbesondere in Kombination mit Informationen zu Ressourcen wie Blütenpflanzen. Die Erhaltung verschiedener Typen naturnaher Lebensräume bietet während der gesamten Saison vielfältige und sich ergänzende Ressourcen, die für die Erhaltung vielfältiger Wildbienengemeinschaften in Agrarlandschaften von entscheidender Bedeutung sind. Insbesondere Massnahmen zur Extensivierung von Wiesen können eine Schlüsselrolle beim Schutz seltener und spezialisierter Arten in diesen Landschaften spielen. Während eine lokal hohe Blütenpflanzenvielfalt die Anzahl und Vielfalt der Wildbienen im Allgemeinen fördert, kann eine bessere Vernetzung der Lebensräume in von Ackerbau dominierten Landschaften den Artenaustausch zwischen lokalen Bienengemeinschaften verbessern. Dies erhöht möglicherweise die Widerstandsfähigkeit der Wildbienengemeinschaften gegenüber Störungen.